“We are at war”: The military rhetoric of COVID-19 in cross-cultural perspective of discourses - Giorgis, Paola; Semenets, Olena; Todorova, Bilyana (Frontiers in Artificial Intelligence, 2023)
At the outburst of the Covid-19 pandemic and all throughout its continuation in 2020 and 2021, the metaphor of ‘war’ has been one of the most pervasive and recurrent globally. As an international, cross-cultural group of scholars and practitioners, we will analyze critically the communicative strategies enacted and the political agenda that they have meant to serve in Italy, Bulgaria, and Ukraine discussing both the cultural differences and the cross-cultural similarities of such a discourse that has been shaping the perception of our factual reality during the pandemic. Expressions like ‘We are at war’, ‘Our heroes are fighting at the forefront’, ‘We will win this war’ and the like contributed to create symbolical cross-cultural responses that, by playing on emotions such as fear, uncertainty and, in some cases, national pride, contributed to the creation of a new state of reality, that of the “new normality”, calling for specific actions and behaviors. However, the war metaphor assumed different hues according to the country in which it was disseminated, up to the actual appointment of generals as governmental spoke-persons or organizers of the vaccine logistics (Todorova 2021; Giorgis 2020-2021), often combined with the construction and the mediatization of the archetypical hero fighting against the virus/enemy (Vovou, 2021). To analyze how, all throughout 2020 and 2021, the military rhetoric was implemented and disseminated as the dominant discourse, we will draw on Media Representations of the Real (Semenets, 2021a), on Rhetoric Studies on Manipulation (Maillat & Oswald, 2009), on Political Discourse (Ilie, 2016; Mavrodieva, 2020), on Critical Discourse Studies (Wodak, 2015), and on Susan Sontag’s fundamental essay Illness as Metaphor (1979). We will discuss such rhetorical strategies also as a part of our collective project In Other Words, an online dictionary that can be used as a free resource in different social and educational contexts (www.iowdictionary.org). The dictionary critically analyzes contextualized keywords which have been shaping different forms of Otherness juxtaposed to some creative proposals to problematize and reverse such narratives.